Highly Crowded Twisted Thienylene‐Phenylene Structures: Evidence for Through‐Space Orbital Coupling in a [4]Catenated Topology. Issue 19 (8th February 2022) - Leitner, Tanja Desirée; von Glasenapp, Jan Simon; Herges, Rainer; Mena‐Osteritz, Elena; Bäuerle, Peter
Abstract: Sterically highly crowded and twisted thienylene‐phenylenes are synthesized and structurally characterized. Single‐crystal X‐ray structure analyses and theoretical studies give evidence of through‐space delocalization of π ‐electrons of peripheral (hetero)aromatic rings in toroidal and catenated topology. Abstract : Sterically highly crowded and twisted thienylene‐phenylenes are synthesized and structurally characterized. Single‐crystal X‐ray structure analyses and theoretical studies give evidence of through‐space delocalization of π ‐electrons of peripheral (hetero)aromatic rings in toroidal and [4]catenated topology (light blue rings).